Hair transplantation surgery - Khanna, Manoj D. (Indian Journal of Plastic Surgery, 2008)
Techniques in hair transplantation have evolved recently which make results look more natural. Hair restoration is one of the most exciting and innovative surgical fields in aesthetic surgery today. A precise appreciation of anatomy has allowed the useof follicular unit grafts. With better methods of harvesting and implantation, hair transplantation results represent a blend of art and science.
Keywords: Hair transplantation; Follicular unit; graft; Kolkata slit